Meatopida gen. nov., a new genus to accommodate two species originally described in Atopida White, 1846 (Coleoptera: Scirtoidea: Scirtidae) - Kiałka, Agata; Ruta, Rafał (Zootaxa, 2018)
The New Zealand species of marsh beetles Atopida dorsale Broun, 1893 and Atopida testacea Broun, 1880 share several features that differentiate them from other members of Atopida White. Analysis of morphological characters and the structural anatomy of the genitalia justified the description of a new genus to accommodate these two species. Sensory structures of the apical maxillary palpomere are described for the first time in Scirtidae. The presence of lacinial hooks in Scirtidae is discussed. Morphology of female prehensors is described and observations of male and female genitalia during copulation are discussed. Lectotypes of both species are designated.